2015
DOI: 10.1097/md.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Rapid Prototyping Technology in Posterior Corrective Surgery for Lenke 1 Adolescent Idiopathic Scoliosis Patients

Abstract: A retrospective study to evaluate the effectiveness of 3-dimensional rapid prototyping (3DRP) technology in corrective surgery for Lenke 1 adolescent idiopathic scoliosis (AIS) patients.3DRP technology has been widely used in medical field; however, no study has been performed on the effectiveness of 3DRP technology in corrective surgery for Lenke 1 AIS patients.Lenke 1 AIS patients who were preparing to undergo posterior corrective surgery from a single center between January 2010 and January 2012 were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 24 publications
1
105
1
4
Order By: Relevance
“…The improved visualization and preparation afforded by the use of individualized models has clinical benefits, with reduced operation time and perioperative blood loss being most commonly reported (11,13,14,(21)(22)(23)(26)(27)(28)30). Reduction in operation time of 15-20% has been reported in multiple studies (11,14,23) across various surgical procedures.…”
Section: Surgical Planningmentioning
confidence: 97%
See 3 more Smart Citations
“…The improved visualization and preparation afforded by the use of individualized models has clinical benefits, with reduced operation time and perioperative blood loss being most commonly reported (11,13,14,(21)(22)(23)(26)(27)(28)30). Reduction in operation time of 15-20% has been reported in multiple studies (11,14,23) across various surgical procedures.…”
Section: Surgical Planningmentioning
confidence: 97%
“…The main reasons given for reduced operation time included a more evolved understanding of the pathology, such as location and surgical approach, and the facilitation of pre-operative instrumentation decisions (14,16,(18)(19)(20)(21)24,27,28,50). Other clinical benefits such as improved diagnosis, reduction in fluoroscopy time, better communication within the surgical team and lower rates of screw misplacement have been reported when compared with the use of conventional imaging in pre-operative planning (11,14,20,26,30). Izatt et al (14) found that the use of a 3DP biomodel improved surgical outcomes in 78% of cases, though this is contradicted by Li et al (23) who reported no change in complication rates or clinical outcomes.…”
Section: Surgical Planningmentioning
confidence: 98%
See 2 more Smart Citations
“…The models had no effect on complication rates, postoperative radiological outcomes or length of hospital stay, and resulted in a 3% overall increase in cost per patient. However, operating room (OR) time was reduced by 13% (184 versus 212 min with versus without models) and blood loss was reduced by 18% [14]. This perhaps highlights an administrative incentive for introducing a clinical 3D printing service in an academic hospital at present, namely performing more operations in a day without reducing the quality of care.…”
Section: Thoracic Applicationsmentioning
confidence: 99%